Untargeted Fecal Metabolomics to Investigate the Role of the Microbiome and Nutrients in Osteoarthritis. (7th June 2021) - Rushing, Blake; McRitchie, Susan; Arbeeva, Liubov; Nelson, Amanda; Azcarate-Peril, M. Andrea; Li, Yuan-Yuan; Qian, Yunzhi; Sumner, Susan; Loeser, Richard
Abstract: Objectives: The objective of this study was to determine if perturbations in gut microbial composition and the gut metabolome could be linked to individuals with obesity and osteoarthritis (OA). Methods: Fecal samples were collected from 92 participants with obesity recruited from the Johnston County Osteoarthritis Project. OA cases ( n  = 59) had radiographic hand plus knee OA, defined as involvement of at least 3 joints across both hands, and a Kellgren-Lawrence (KL) grade 2–4 in at least one knee. Controls ( n  = 33) were without hand OA and with KL grade 0–1 knees. Fecal metabolomes were analyzed by a UHPLC/Q Exactive HFx mass spectrometer. Microbiome composition was determined in fecal samples by 16S ribosomal RNA amplicon sequencing (rRNA-seq). Stepwise logistic regression models were built to determine predictors of OA status. Spearman correlations were performed to determine associations between metabolites and microbiota in OA or healthy individuals. Results: Untargeted metabolomics analysis indicated that OA cases had significantly higher levels of di- and tri-peptides ( P < 0.05), and significant perturbations ( P  < 0.1) in microbial metabolites. Pathway analysis revealed several significantly perturbed pathways ( P < 0.05) associated with OA, including leukotriene metabolism, amino acid metabolism and fatty acid utilization. Logistic regression models selected metabolites associated with the microbiota and leaky gut syndrome as significant predictors of OA status, particularly when combined with the 16S rRNA sequencing data. Omega-3/6 polyunsaturated fatty acids (PUFAs) levels were significantly correlated with the phyla Bacteriodetes and Firmicutes . Conclusions: Adults with obesity and OA have distinct fecal metabolomes characterized by perturbations in microbial metabolites, PUFAs, and protein digestion compared with healthy controls. These metabolic perturbations suggest a role of intestinal inflammation and leaky gut in OA. Funding Sources: Supported by the Arthritis Foundation, the National Center for Advancing Translational Sciences (NCATS) (UL1TR002489), and the National Institute of Arthritis and Musculoskeletal and Skin Diseases (P30AR072580).